2010
DOI: 10.1021/jp110400t
|View full text |Cite
|
Sign up to set email alerts
|

OH Radical Scavenging Activity of Edaravone: Mechanism and Kinetics

Abstract: The reactions of OH radicals with the neutral and anionic forms of Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one, EDA) have been studied using Density Functional Theory. Different mechanisms and reaction sites have been considered. The overall rate constant was found to be diffusion-limited (1.35 × 10(10) M(-1) s(-1), in aqueous solution), and in excellent agreement with the experimental results. Therefore, the present work supports previous evidence that EDA is an excellent (•)OH scavenger. The anionic form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 66 publications
(89 reference statements)
5
83
0
3
Order By: Relevance
“…The derivative referred to as C1 in this work (3-(4-(3-methyl-5-oxo-4,5-dihydro-1-pyrazol-1-yl) phenoxy) propyl nitrate; Scheme 1) was found to be among the best ones. This is in agreement with previous results from our group based on the electron-donating capability and ease of deprotonation for a large set of EDA derivatives, [44] as well as on the kinetic of their single electron transfer (SET) reactions with free radicals of different nature in aqueous solution. [45] In both works, C1 was found to be one of the best possible free radical scavengers among the studied EDA derivatives.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…The derivative referred to as C1 in this work (3-(4-(3-methyl-5-oxo-4,5-dihydro-1-pyrazol-1-yl) phenoxy) propyl nitrate; Scheme 1) was found to be among the best ones. This is in agreement with previous results from our group based on the electron-donating capability and ease of deprotonation for a large set of EDA derivatives, [44] as well as on the kinetic of their single electron transfer (SET) reactions with free radicals of different nature in aqueous solution. [45] In both works, C1 was found to be one of the best possible free radical scavengers among the studied EDA derivatives.…”
Section: Introductionsupporting
confidence: 93%
“…[34,84] The prevailing one among them is the keto form, with a population~97%. [85] Therefore, it Scheme 1. EDA derivatives, C1 and D1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, the computational results are expected to interpret the experimental findings and provide theoretical support for the conclusions of the experimental MPB degradation results. In addition, as a approach of cost-effective, convenient, and avoiding the use of animals for toxicological study [22,23], computational approach is frequently adopted to investigate the molecular basis of environmental, chemical, and biological processes [24,25]. To date, no computational study has been reported on the mechanisms and kinetics of MPB degradation using AOPs, as well as the toxicity assessment of its degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…More recently in the Truhlar group (University of Minnesota) new DFT methods have been developed that can achieve the required accuracy for kinetic and thermodynamic calculations without the need of refining energies with post Hartree-Fock methods. This is the case of the M05-2X functional that we have adopted for some of our recent studies (Zavala-Oseguera et al, 2009;Galano et al 2011Pérez-González & Galano 2011;Leon-Carmona & Galano, 2011;Galano 2011;Gao et al, 2010;.…”
Section: B//a Approachmentioning
confidence: 99%